Effectiveness of national multicentric school-based health lifestyles intervention among chinese children and adolescents on knowledge, belief, and practice toward obesity at individual, family and schools' levels - Wang, Xinxin; Liu, Jieyu; Gao, Di; Li, Yanhui; Ma, Qi; Chen, Li; Chen, Manman; Ma, Tao; Ma, Ying; Zhang, Yi; Yang, Jianjun; Dong, Yanhui; et al. (Frontiers in Pediatrics, 2022)
Abstract Background: This study aims to evaluate the effectiveness of the trial of national multicentric school-based health lifestyles intervention towards childhood obesity on the KBP at individual, family and schools’ levels. Methods: The national trial was a multi-centered, cluster-controlled trial, which was conducted in seven provinces from September 2013 to February 2014, aiming at preventing childhood overweight and obesity. Integrated intervention strategies focused on changing specific practice related to energy intake and expenditure, such as decreasing the consumption of sweetened fizzy drinks, increasing the consumption of vegetables, ensuring proper protein intake, reducing sedentary practice including screen time, and maintaining at least 1 h of moderate to vigorous physical activity. A total of 27477 children and adolescents in the control group and 30997 in the intervention group were recruited with a mean follow-up period of 6.7 months. The binomial response mixed-effects model was used for assessing the effects of the national school-based health lifestyles intervention on obesity-related KBP at students individual, parents’ and schools’ levels. Results: Children and adolescents in the intervention group mastered better obesity-related knowledge, and they had higher correct response rates to all questions about obesity-related knowledge compared to the control group (P<0.05). In terms of obesity-related belief, individuals in the intervention group was more motivated than the control group, participants in the intervention group had higher correctness of 71.18%, 52.94%, and 56.60% than the control group of 68.61%, 49.86%, and 54.43%, (P<0.05). In addition, healthier habits of eating breakfast and drinking milk every day were observed in the intervention group. For the beliefs towards obesity, parents of the intervention group had higher correctness than the control group. At the same time except for the fruit consumption, other obesity-related practice in the intervention group were healthier than the control group (P <0.05). Except for some beliefs and practice, the intervention effect at the parent level was not significant in other aspects. Conclusions: The obesity-related knowledge and beliefs of children and adolescents got improved significantly. However, the effects on the knowledge, beliefs and certain practices of their parents and school administrators failed to reach significance.